2013
DOI: 10.1016/j.jim.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing monoclonal antibodies against ricin's enzymatic subunit interfere with protein disulfide isomerase-mediated reduction of ricin holotoxin in vitro

Abstract: The penultimate event in the intoxication of mammalian cells by ricin toxin is the reduction, in the endoplasmic reticulum (ER), of the intermolecular disulfide bond that links ricin’s enzymatic (RTA) and binding (RTB) subunits. In this report we adapted an in vitro protein disulfide isomerase (PDI)-mediated reduction assay to test the hypothesis that the RTA-specific neutralizing monoclonal antibody (mAb) IB2 interferes with the liberation of RTA from RTB. IB2 recognizes an epitope located near the interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Unfortunately, our current report does not address the mechanism(s) by which the supercluster II antibodies neutralize ricin. We can only speculate that they interfere with a region of the toxin that is required for retrograde transport from the plasma membrane to the ER and/or retrotranslocation from the ER to the cytoplasm (45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our current report does not address the mechanism(s) by which the supercluster II antibodies neutralize ricin. We can only speculate that they interfere with a region of the toxin that is required for retrograde transport from the plasma membrane to the ER and/or retrotranslocation from the ER to the cytoplasm (45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to ricin, a sister protein of abrin, have been demonstrated to exert neutralization by hindering cell surface attachment of ricin 19 or inhibiting the catalytic activity of the A chain 20 or interfering with the reduction of the holotoxin to A and B chains. 21 It is less likely that mAb A7C4 acts via the last mechanism as the epitopic region is present away from the interface between the A and B chains. All the observations mentioned above strongly suggest an alternate mechanism of neutralization of abrin by the mAb A7C4.…”
Section: Discussionmentioning
confidence: 99%
“…Legler and colleagues recently demonstrated, using V H Hs, a correlation between an antibody's impact on RTA unfolding dynamics and in vitro toxin-neutralizing activity, possibly due to events associated with ricin endocytosis or retrograde transport (39). Other reports have shown that anti-RTA MAbs reduced intracellular transport of ricin from the plasma membrane to the endoplasmic reticulum (ER) and even prevented protein-disulfide isomerase (PDI)-mediated dissociation of RTA from RTB in a cell-free assay (62)(63)(64). Whether these in vitro activities are relevant in vivo The strongly protected regions for each cluster are summed over all MAbs belonging to that cluster and shown mapped to the crystal structure of the ricin holotoxin (PDB ID: 2AAI) (14), with each cluster colored as indicated.…”
Section: Discussionmentioning
confidence: 98%